PENGARUH BUDAYA ORGANISASI, KOMUNIKASI INTERPERSONAL, DAN MANAJEMEN KONFLIK TERHADAP EFEKTIVITAS PENGAMBILAN KEPUTUSAN DI SMK SWASTA KECAMATAN PAMULANG - Fathia Salsabila; Yulita Puji Lestari; R. Dede Siswandi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the influence of organizational culture, interpersonal communication, and conflict management on the effectiveness of decision making at private vocational high schools in Pamulang District, both partially and simultaneously. This study used a quantitative approach with a correlational survey method. The population and sample of this study consisted of 154 respondents, namely teachers at private vocational high schools in Pamulang District. Data were collected through a Likert-scale questionnaire and analyzed using simple and multiple linear regression techniques with the assistance of SPSS software. The results show that organizational culture has a positive and significant effect on the effectiveness of decision making by 32.1% (R = 0.566; t = 8.473; p < 0.001); interpersonal communication has a positive and significant effect by 42.5% (R = 0.652; t = 10.597; p < 0.001); and conflict management has a positive and significant effect by 60.7% (R = 0.779; t = 15.314; p < 0.001) and is the most dominant variable. Simultaneously, the three variables have a positive and significant effect on the effectiveness of decision making by 61.8% (R = 0.786; F = 80.331; p < 0.001), while the remaining 38.2% is influenced by other factors outside this study. The results of the multiple regression test and the Effective Contribution calculation show that conflict management provides the largest contribution (52.12%), while organizational culture no longer provides a significant unique contribution when analyzed together with the other two variables. This study concludes that conflict management is a key factor in improving the effectiveness of decision making at private vocational high schools, so it is recommended that schools strengthen constructive conflict management mechanisms to support a more effective decision-making process.